(3GdKbI GdYGWajI (B:s (3CHSW GdNWhGJ dEOGQI eTGYQc (B/s - (3dfOfajdO, Ljds ((3GdQjGV (B:s (3ecJHI LQjQ,s, 2004)
(3jTQM GdcJGH CSS HfGA GdKbI GdYGWajI(B.s
Keywords: (3GdYhGWas; (3GdTYhQs; (3GdKbI HGdfaSs